Deskripsi Kualitas Minyak Goreng Hasil Pemanasan - Zuliyama; Rahmanpiu; Wa Ode Mulyana (Sains: Jurnal Kimia dan Pendidikan Kimia, 2023)
A research entitled description of cooking oil quality resulted from heating. This study aims to describe the quality of cooking oil produced by heating. This research is a quantitative descriptive which tests on 3 variables, namely water content, free fatty acid content and peroxide value of cooking oil before and after heating. Water content was determined by thermogravimetry method, free fatty acid content was determined by alkalimetric titration method (KOH) and the peroxide number was determined by iodometric method. The results showed that in determining the water content, the three types of oil met the SNI 7709 (2019) standard with the value of packaged oil I, packaged oil II and bulk oil respectively 0.1197%, 0,0749% and 0,1048%. In determining the free fatty acid content without heating, none met the SNI 7709:2019 standard, while in the determination of the free fatty acid content after heating, the three types of oil met the SNI 7709 (2019) standard with successive values of 0.334%, 0.2319% and 0.3141%. In determining the peroxide value without heating, the three types of oil met the SNI 7709 (2019) standards with successive values of 6.7217 mek O2/kg, 8.7664 mek O2/kg and 9.6556 mek O2/kg, while in determining the peroxide number after heating, only oil packaged II cooking oil and bulk cooking oil that meet the SNI 7709 (2019) standards with values of 7.8949 mek O2/kg and 9.6556 mek O2/kg respectively.